Lovastatin Biosynthesis by Aspergillus terreus in a Chemically Defined Medium - Hajjaj, Hassan (American Society for Microbiology, 2001)
Lovastatin is a secondary metabolite produced by Aspergillus terreus. A chemically defined medium was developed in order to investigate the influence of carbon and nitrogen sources on lovastatin biosynthesis. Among several organic and inorganic defined nitrogen sources metabolized by A. terreus, glutamate and histidine gave the highest lovastatin biosynthesis level. For cultures on glucose and glutamate, lovastatin synthesis initiated when glucose consumption levelled off. When A. terreus was grown on lactose, lovastatin production initiated in the presence of residual lactose. Experimental results showed that carbon source starvation is required in addition to relief of glucose repression, while glutamate did not repress biosynthesis. A threefold-higher specific productivity was found with the defined medium on glucose and glutamate, compared to growth on complex medium with glucose, peptonized milk, and yeast extract.